High-temperature stable plasmonic and cavity resonances in metal nanoparticle-decorated silicon nanopillars for strong broadband absorption in photothermal applications. Issue 31 (29th July 2019) - Hou, Guozhi; Wang, Zhaoye; Ma, Haiguang; Ji, Yang; YU, Linwei; Xu, Jun; Chen, Kunji
Abstract : Hybrid metal nanoparticle-decorated Si nanopillars with proper Al2 O3 encapsulation to accomplish high-temperature stable and highly efficient photothermal applications. Abstract : Plasmonic metal nanoparticles in conjunction with the cavity mode resonance in crystalline silicon (c-Si) nanopillars (NPs) can help achieve strongly enhanced broadband light absorption far beyond the limit of bulk c-Si. However, a major concern arises from the stability of metal nanoparticles, particularly at a high temperature, as the diffusion and conglomeration of the nanoparticles will undermine the very basis for the advantageous plasmonic effect. We here carried out a systematic investigation of the thermal stability of different metal nanoparticles coated on 3D Si-based NPs and found that simple Al2 O3 encapsulation could help stabilize the gold (Au) particles coated on Si NPs even when subjected to annealing at >1073 K while accomplishing excellent broadband optical absorption (∼95%) from 200 nm to 2500 nm. This could be assigned mainly to the excellent dispersion retention capability of the Al2 O3 -encapsulated Au nanoparticles and the beneficial plasmon resonance absorption among the Au nanoparticles and Si NPs, as also revealed from the FDTD simulation analysis. Finally, a rapid vapor generation application was demonstrated based on the optimized Au/Si NPs, where salt water drops could be directly injected onto the high-temperature photo-heated Au/Si NPs and could vaporize/bounce off quickly without leaving any salt precipitation on the surface. This new strategy can also pave the way for high-performance Si-based photothermal applications.